Optimizing HVAC System Performance and Comfort: A Numerical Investigation of Air Inlet Placement - Aekarrechai Pattawee; Vongsoasup Naphatsorn; Charoensin-O-Larn Roytor (E3S Web of Conferences)
Given the significant impact of indoor air quality (IAQ) on human health, regulations and standards have been imposed to maintain high air quality. Conformity with regulations necessitates ventilation, a process that significantly consumes energy. This study employs computational methods to analyze the temperature distribution inside the breathing zone and evaluate the effectiveness of the air supply setup in an office environment. The investigation relies on the widely utilized metric referred to as the age of air. This study analyzes three different inlet configurations while maintaining a constant airflow rate. The results indicate that the age of air decreases when the air inlet is situated in a central location. Conversely, positioning the supply air inlet at the lowest elevation results in the most uniform temperature distribution, which is crucial for occupant comfort. The findings suggest that changing the airflow rate in systems with minimal air duration can enhance the energy efficiency of HVAC systems.